Infrastructure and its role in the transformation of e-learning From the viewpoint of the faculty members of the Faculty of Natural Resources Engineering, Bir El-Ghanem, Zawia University - Mansour , F.; Abdulsadiq , M.; Khalfallh , A. (Journal of Pure & Applied Sciences, 2021)
The study aims to identify the infrastructure and its role in the transformation of e-learning from the viewpoint of the faculty members in the College of Natural Resources Engineering / Bir Al-Ghanim at Zawia University Also، to emphasize the need for infrastructure to be available and modernized and to be in line with today’s requirements. A comprehensive survey questionnaire is distributed to all the 35 faculty members of the study population and 33 questionnaires were received back. Among the 33 questionnaires collected، there was one questionnaire that contains incomplete data، therefore، was excluded from further analysis. All statistical analysis was carried out using the statistical package for social sciences (SPSS v22). Results indicate that the existence of a statistically significant positive relationship between the importance of the infrastructure and the transformation of e-learning. This indicates، the more infrastructure there، the greater the achievement of the transformation of e-learning. The study recommended working on the development of the infrastructure for the transformation of e-learning، such as providing (Classroom accessories، electronic laboratories، and virtual laboratories). Besides، providing modern computers that are permanently connected to the Internet